DATA SECURITY STRATEGY BASED ON STORED PROGRAMS: A CASE STUDY OF DSS FOR TEACHING ASSISTANT SELECTION - Ciptadi, Prahenusa Wahyu; Tri Hastono; Kharismajati, Gema; Syah, Firdiyan; Fahriza, Nayaka Anung (JTH: Journal of Technology and Health, 2024)
Data security is becoming increasingly crucial in information system management, especially in academic environments that handle sensitive information. The reliance on digital systems demands the protection of data integrity, confidentiality, and availability. High-level data security is also required in the Decision Support System (DSS) application for selecting Teaching Assistants at Universitas PGRI Yogyakarta. The DSS helps determine candidates based on GPA, experience, and skills. However, this system is vulnerable to threats such as unauthorized data modifications, access abuse, SQL Injection, and cyber-attacks that can impact decision-making. Stored Programs in databases provide an effective solution to enhance data security. This research aims to design Stored Programs as a security strategy for data input into database tables. The types of Stored Programs designed in this study include Stored Procedures, Functions, and control programs. The design methodology for the Stored Programs follows the waterfall method. The test results indicate that the Stored Programs function as expected and execute in a very short time. The execution of Stored Programs takes only 0.0059 seconds.